0.3 v Fully Differential Current Conveyor Using MIBD-DT MOST technique - Kumngern, Montree; Torteanchai, Usa; Wongprommoon, Natapong; Jongchanachavawat, Wirote; Tooprakai, Siraphop; Lerkvaranyu, Somkiat (My University, 2022)
This paper presents a new fully differential second-generation current conveyor (FDCCII) using multiple-input bulk-driven dynamic threshold voltage MOS transistor (MIBD-DT MOST) technique. This FDCCII, the MOST techniques such as the multiple-input (MI), bulk-driven (BD) and dynamic threshold voltage (DT) have been used. The MIBD can be reduced the number of differential pair of FDCCII and the DT-MOST technique can be reduced the power supply requirement. Thus, the proposed FDCCII is capable to working with a supply voltage of 0.3 V and it consumes a 0.132 uW of power dissipation. The simulations were performed with SPICE program using the 0.18 um CMOS technology. To prove the workability of the new circuit, the proposed FDCCII has been used to realize universal filter.
Keywords: dynamic threshold voltage MOS transistor; fully differential current conveyor; multiple-input MOS transistor